Research into the design of distributed directory services - Benford, Steven David (1988)
Distributed, computer based communication is becoming established within many working environments. Furthermore, the near future is likely to see an increase in the scale, complexity and usage of telecommunications services and distributed applications. As a result, there is a critical need for a global Directory service to store and manage communication information and therefore support the emerging world-wide telecommunications environment. This thesis describes research into the design of distributed Directory services. It addresses a number of Directory issues ranging from the abstract structure of information to the concrete implementation of a prototype system. In particular, it examines a number of management related issues concerning the management of communication information and the management of the Directory service itself. The following work develops models describing different aspects of Directory services. These include data access control and data integrity control models concerning the abstract structure and management of information as well as knowledge management, distributed operation and replication models concerning the realisation of the Directory as a distributed system. In order to clarify the relationships between these models, a layered directory architecture is proposed. This architecture provides a framework for the discussion of directory issues and defines the overall structure of this thesis. This thesis also describes the implementation of a prototype Directory service, supported by software tools typical of those currently available within many environments. It should be noted that, although this thesis emphasises the design of abstract directory models, development of the prototype consumed a large amount of time and effort and prototyping activities accounted for a substantial portion of this research. Finally, this thesis reaches a number of conclusions which are applied to the emerging ISO/CCITT X. 500 standard for Directory services, resulting in possible input for the 1988-92 study period.